2018
DOI: 10.1186/s12957-018-1320-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of miR-198-5p in lung squamous cell carcinoma assessed using microarray and RT-qPCR

Abstract: BackgroundTo examine the clinical value of miR-198-5p in lung squamous cell carcinoma (LUSC).MethodsGene Expression Omnibus (GEO) microarray datasets were used to explore the miR-198-5p expression and its diagnostic value in LUSC. Real-time reverse transcription quantitative polymerase chain reaction was used to evaluate the expression of miR-198-5p in 23 formalin-fixed, paraffin-embedded (FFPE) LUSC tissues and corresponding non-cancerous tissues. The correlation between miR-198-5p expression and clinic patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Otherwise, a random-effects model was applied (I 2 >50%) ( 45 ); meanwhile, heterogeneity analysis was performed to discover the sources of heterogeneity. Subsequently, a summary (s)ROC was created to indicate the ability of miR-193a-3p to identify TC compared with a normal sample ( 46 48 ).…”
Section: Methodsmentioning
confidence: 99%
“…Otherwise, a random-effects model was applied (I 2 >50%) ( 45 ); meanwhile, heterogeneity analysis was performed to discover the sources of heterogeneity. Subsequently, a summary (s)ROC was created to indicate the ability of miR-193a-3p to identify TC compared with a normal sample ( 46 48 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, decreased expression of miR-198-5p was observed in lung squamous cell carcinoma tissues (SMD, −0.34; 95% CI, −0.71–0.04) (49). For LUAD, miR-198-5p initially received attention due to its differential expression between benign pleural effusion and LUAD-associated malignant pleural effusion (LA-MPE).…”
Section: Discussionmentioning
confidence: 95%
“…Diagnostic odds ratio, as well as negative and positive likelihood ratios, were also analyzed. In addition, the present study performed sROC analysis to further appraise the distinguishing ability of miR-132-3p (2628). Thirdly, a Kaplan-Meier analysis was conducted to reveal the prognostic ability of miR-132-3p in CCA based on TCGA data, and a log-rank test was performed to compare the survival between high and low miR-132-3p expression groups.…”
Section: Methodsmentioning
confidence: 99%